Predictors of Successful Tobacco Cessation After Receiving an E-Cigarette Based Smoking Cessation Intervention - Ian Pope; Allan Clark; Lucy Clark; Emma Ward; Susan Stirling; Pippa Belderson; Caitlin Notley (SAGE Publishing, 2024)
Introduction E-cigarettes have been shown to be effective for tobacco smoking cessation. Predicting those who are most likely to achieve smoking abstinence after receiving an e-cigarette based smoking cessation intervention could help to target interventions more efficiently. Methods A secondary analysis of baseline characteristics of 505 people who received an emergency department based smoking cessation intervention incorporating brief advice, provision of an e-cigarette starter kit and referral to stop smoking services. Gender, ethnicity, age, employment status, deprivation, partner smoking status, cigarettes per day, motivation to quit, cigarette dependence and previous e-cigarette use were assessed as predictors of abstinence. Self-reported smoking status was collected 6 months after intervention delivery. Results At 6 months 169/505 (33%) of those who received the intervention self-reported abstinence. The groups that were more likely to report having quit were females (37.4% of females vs 31.0% of males), older people (41.1% of over 50s vs 33.3% of under 35s), lighter smokers (36.4% of those who smoked less than 10 cigarettes per day vs 30.7% for those who smoked over 20) and more motivated quitters (35.6% for those with high motivation vs 29.2% for those with low motivation). However, in multiple logistic regression, when adjusting for the other factors, no factors significantly predicted smoking abstinence. Degree of nicotine dependence was very similar between those who quit and those who did not. Conclusion The study found no baseline factors that could predict successful smoking cessation with e-cigarettes. Consequently, this study does not support the use of a targeted e-cigarette-based smoking cessation intervention, suggesting the adoption of a more universal approach.